2019
DOI: 10.3389/fimmu.2019.02071
|View full text |Cite
|
Sign up to set email alerts
|

CXCR5+PD1+ICOS+ Circulating T Follicular Helpers Are Associated With de novo Donor-Specific Antibodies After Renal Transplantation

Abstract: Donor-specific anti-HLA antibodies (DSAs) are a major risk factor associated with renal allograft outcomes. As a trigger of B cell antibody production, T follicular helper cells (Tfhs) promote DSA appearance. Herein, we evaluated whether circulating Tfhs (cTfhs) are associated with the genesis of antibody-mediated rejection. We measured cTfh levels on the day of transplantation and 1 year after transplantation in blood from a prospective cohort of 237 renal transplantation patients without DSA during the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…DSA has been associated withboth acute and chronic rejection in solid organ allografts, and DSA is one of the major causes of chronic rejection in solid organ transplantation 39,40 . The roles of blood circulating CXCR5 + ICOS + CD4 + T cells in de novo DSA antibody responses has been reported in renal allograft recipients 41 . Another study also reported that PD-L1 expressed on Bregs can also suppress antibody responses 30 , but the mechanisms for the Breg PD-L1-mediated suppression of antibody response remain to be fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…DSA has been associated withboth acute and chronic rejection in solid organ allografts, and DSA is one of the major causes of chronic rejection in solid organ transplantation 39,40 . The roles of blood circulating CXCR5 + ICOS + CD4 + T cells in de novo DSA antibody responses has been reported in renal allograft recipients 41 . Another study also reported that PD-L1 expressed on Bregs can also suppress antibody responses 30 , but the mechanisms for the Breg PD-L1-mediated suppression of antibody response remain to be fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…ICOS is essential for Tfh development and plays important roles in B‐cells maturation and activation by combining ICOS‐L expressed on B cells [43]. Circulating ICOS+PD‐1+Tfh cells had been reported to play important roles in several diseases [44, 45]. In addition, our results also showed that the proliferation indicator Ki‐67 was higher in AAV patients, suggesting that Tfh cells are much more active in MPA patients, although the level of Tfh cells is not elevated.…”
Section: Discussionmentioning
confidence: 60%
“…The FaDA application allows users to profit from various data visualization options given a glance of data analysis, identifying significant findings and possibly highlighting outliers with limited time consumption. We have used two cases study from previously published datasets (16,18) to exhibit the usefulness of FaDA for common data generated from non-computational researchers; that entails microarray and flow cytometry. Note that despite FaDA proposal of various statistical options, it cannot replace recommendations from a statistician that users may need for particular cases as for any analysis software.…”
Section: Discussionmentioning
confidence: 99%